Pengaruh Penyambungan PLTMH Terhadap Tegangan Jatuh pada Penyulang BBLA - Anto Carmanto; Ojak Abdul Rozak; Yusup Muhammad Syakir (OKTAL : Jurnal Ilmu Komputer dan Sains, 2025)
Micro hydro power plants (PLTMH) are environmentally friendly alternative plants at PT. PLN ULP Pamempeuk has one of the feeders that is synchronized with PLTMH to increase power to the feeder. In some of these channels, there is a voltage drop that exceeds the standard limit of SPLN number 73 in 1987, it was 5%. In this thesis, a calculation was made of the magnitude of the voltage drop before and after it was interconnected with the PLTMH. From the calculation results before being interconnected with the PLTMH, there were four substations that experienced voltage drops, namely Substation WNGC-1018 by 6.585%, BOJ-441 by 5.825%, SUK-024 by 6.815%, and TLL-882 by 6.110%. To reduce the voltage drop, in addition to being synchronized with PLTMH, PLN also added two substations, namely the CPKP–999 substation with a transformer capacity of 100 kVA to reduce the voltage drop at the WNGC–1018 substation to 2.514%, then the KCU-808 substation with a transformer capacity of 100kVA to reduce the voltage drop at the SUK-024 substation to 4.284%. Then, the results of the calculation after being interconnected with the PLTMH, there are two substations that are still experiencing voltage drops, namely 1,272,076 volts with a percentage of 6.360% at substation B0J - 441 and 1,243,193 Volts with a percentage of 6.215% at substation TTL-882. Then, the repair solution that is carried out is to relocate the substation location. The substations that have changed locations are BOJ substation – 441 from 22,900 kms to 11,484 and TLL-882 substation from 23,650 kms to 9,802 kms. This location change reduces the voltage drop in the two substations, where previously the BOJ-441 substation had a voltage drop to 319.856 volts with a percentage decrease from 6.360% to 1.599% and in the TLL-882 substation, the voltage fell to 213.533 volts with a percentage decrease from 6.215% to 1.067%.